Management of Local Anesthetics Systemic Toxicity in a 66-Year-Old Male Undergoing Nephrostomy Percutaneous - Andi Nugroho; Restian Rudy Oktavianto (Faculty of Medicine, Brawijaya University, 2022)
Background: Neuraxial anesthesia compares favourably with other systemic and regional methods about safety and efficacy. The complications related to neuraxial anaesthesia including transient neurological symptoms, inadvertent intrathecal injection and cardiac arrest. Local anesthetics systemic toxicity (LAST) is one of a life-threatening complication when the effects of local anesthetics reach the systemic circulation.Case: We report a local systemic toxicity on 66-year-old male who underwent bilateral nephrostomy percutaneous. Patient were hemodynamically stable and were placed in supine position, preoperatively. Head-to-toe examination showed an increased bronchial breath sounds and rough crackles in the 4-5 left and right intercostal space. Laboratory examinations revealed anemia (Hb 10.6 g/dl) and impairment on kidney function (ureum 148 mg/dl; creatinine 4.9 mg/dl). Patient were planned to do an epidural at the level of L2 - L3 with a 14 ml levobupivacaine 0.5% in incremental doses 5 mg - 5 mg – 4 mg. Shortly after receiving the third incremental doses of levobupivacaine the patient experienced in disruption on cardiovascular and neurovascular system which showed as persistent bradycardia and loss of consciousness. Patient decided to undergo general anesthesia with lipid emulsion infusion and showed an improvement afterwards.Conclusion: The main principle of LAST management is to ensure adequate ventilation and organ perfusion with sufficient oxygen-rich-blood to perfuse on brain, heart, and kidneys to prevent acidosis until lipid emulsion therapy. LAST management requires prompt and precise diagnosis and treatment to get a good outcome.